Literature Review – Analisis Faktor Ketidaklengkapan Pengisian Resume Medis Pasien Rawat Inap - Oky Hermawan Saputra (Universitas Duta Bangsa Surakarta, 2021)
Medical resume is a summary of the entire period of care and treatment performed by health workers to patients. An incomplete medical resume will have an impact on detailed information about what happened during the time the patient was hospitalized so that it will also have an impact on the quality of the medical record itself and the services provided by the hospital. This study is a literature review study which aims to analyze the factors that cause incomplete filling of inpatient medical resumes. The type of research using literature review from 16 articles included 1 article quantitative, 7 descriptive articles, 7 quantitative descriptive articles, 1 quantitative qualitative article.The causes of incompleteness in filling out medical resumes that were found included inadequate accuracy and discipline of officers, lack of knowledge of officers, poor attitude of officers, immature age of officers, types of medical personnel expertise that did not match patients when filling out medical resumes, the working period is still small, the employment status is not right, the number of officers is insufficient, the facilities are not maximal, the infrastructure is inadequate, the absence of Standard Operating Procedures (SOP) regarding filling out medical resumes, the absence of rewards and punishments, the socialization of policies and regulations has not optimal and the job description is not clear. Efforts that can be made are training, socialization and periodic monitoring, calculating workloads, creating separate spaces for processing medical records and making SOPs for filling out medical resumes.